Aerobic phenol degradation using native bacterial consortium via ortho–and meta–cleavage pathways - Shebl, Sara; Ghareeb, Doaa A.; Ali, Safaa M.; Ghanem, Nevine Bahaa El Din; Olama, Zakia A. (Frontiers in Microbiology, 2024)
Novelty and significance of the present work which would attract many researchers' attention: -This study represents the pioneering effort in investigating the degradation of phenol in contaminated environments through utilization of bacterial consortium that effectively activates both meta-and ortho-cleavage pathways simultaneously. The results obtained not only validate the efficacy of this approach, but also provide novel insights into the enzymatic and molecular mechanisms involved. This research contributes significantly to the understanding of phenol degradation in phenol-contaminated environments and paves the way for future advancements in this field. -We confirm that neither the manuscript nor any parts of its content are currently under consideration or published in another journal. -All authors have approved the manuscript and agree with its submission to your esteemed journal.